In Vitro Antidermatophytic and Biochemical Studies on Aqueous Extracts of Avicennia marina and Suaeda monoica Plants from the Yanbu Region - Manal O. Alkattan; Enas N. Danial; Wafa A. Alshehri; Fathia El Halawany; Njood A. Alzumay (Journal of Pure and Applied Microbiology, 2022)
Many infectious diseases can be treated using herbal medicines. Therefore, plant materials play a major role in therapeutic medicine and are widely used in many developing countries. In this study, we analyzed the potential of Avicennia marina and Suaeda monoica leaf extracts as antidermatophytic agents. Molecular identification of the plant samples was performed via DNA sequencing of the internal transcribed spacer region using the primers ITS-u1 and ITS-u4. Leaf extracts of A. marina and S. monoica were prepared in cold and hot distilled water. Their antidermatophytic activities were evaluated against Trichophyton mentagrophytes, T. verrucosum, Microsporum gallinae, M. gypseum, M. canis, Epidermophyton floccosum, Candida albicans, and C. tropicalis using the dry weight method. E. floccosum was the most sensitive to both cold extracts of A. marina and S. monoica, whereas T. verrucosum was the most sensitive to the hot extract of A. marina. The minimum inhibitory concentrations of the hot extracts were determined. They ranged from 10 to 30 mg/ml, defining the anti-scavenging activity and total phenolic content of both plants. The hot extract of A. marina possessed the highest anti-scavenging activity (76%), whereas the cold extract of A. marina contained the highest phenolic content (40.06 mg/g dry weight). In addition, high-performance liquid chromatography was used to separate and estimate some of the bioactive compounds present in the plant extracts.